A template for a clinico-pathological audit of medical liver biopsies. Issue 11 (27th July 2015) - Colling, Richard; Fryer, Eve; Cobbold, Jeremy; Collier, Jane; Collantes, Elena; Wang, Lai Mun; Hubscher, Stefan; Wyatt, Judith; Fleming, Kenneth
Abstract : Aims: With changing indications for performing medical liver biopsies, we aimed to develop a tool to allow pathologists to evaluate the current usefulness, value and impact of their medical liver biopsy service. Methods: We designed and piloted a questionnaire-based clinico-pathological audit for medical liver biopsies. Results: The audit tool was simple to implement and provided useful information about our service. Hepatologists felt that 96% of reports were clinically useful. 56% of biopsies confirmed clinical diagnoses, 46% helped differentiate between diagnoses and 42% were able to exclude possible diagnoses. 74% resulted in a change of management and 27% of liver biopsies resulted in a diagnosis which was not clinically suspected. Conclusions: We demonstrate the usefulness of an audit tool in providing evidence of the value of the liver pathology service in a large UK regional centre.